STRATEGIES THAT FAVOR MYCORRHIZATION IN THE REFORESTATION OF A DISTURBED AREA IN THE SEMIARID REGION - Gomes Costa, Mirian Cristina; de Abreu Vasconcelos, Mario Rógeson; Pontes Filho, Roberto Albuquerque; Alves Lima, Luan; Martins Melo, José Lucas; Mendes Filho, Paulo Furtado (Floresta, 2021)
Hydrogel and mulch added to the soil may favor arbuscular mycorrhizal fungi (AMF), contributing to the reforestation of disturbed lands in semiarid regions. This study aimed to evaluate AMF colonization in the roots of Enterolobium contortisiliquum (Vell.) Morong in response to the application of hydrogel and mulch (bagana) from carnauba palm (Copernicia cerifera L.) to the soil and their effects in the soil and plants. A field experiment was set up in April 2014 in Ibaretama (Ceará, Brazil) in a randomized block design in a 2×4 factorial scheme – with mulch (+M) e without mulch (−M) × hydrogel doses (0, 4, 5, and 6 g L−1) –, with five replicates. Samples of roots, soil, and leaves were collected 18 months after the beginning of the experiment to determine AMF colonization in the roots and nutrient contents in the soil and plant material. The hydrogel dose of 6 g L−1 and mulch application equivalent to 10 Mg ha−1 increased AMF colonization by 21 e 44%, respectively. Soil contents of Ca, K, and Zn decreased with hydrogel doses without mulch but increased in the presence of the carnauba palm residue applied as mulch. A higher P content in the plant material was not associated with AMF colonization. The leaf content of Ca responded only to the treatment with mulch, reaching the highest value (3.8 g kg−1) in the absence of mulch.